Counselling Approaches and Educational Support for Business Education in Students with Visual and Hearing Impairments: Enhancing Accessibility and Learning Outcomes (British Journal of Multidisciplinary and Advanced Studies, 2024)
This qualitative study delves into the counselling and educational support for Nigerian business education students with visual and hearing impairments through interviews with 15 professionals, including educators, counsellors, and administrators. It reveals a critical lack of accessible educational resources and assistive technologies, highlighting the suboptimal effectiveness of existing support due to insufficient trained staff. Professionals suggest a comprehensive approach to improvement, advocating for the creation of accessible materials, enhanced training, investment in technologies, and policy reforms to overcome these barriers. The study calls for immediate systemic changes to facilitate better accessibility and proposes future research to encompass longitudinal studies, the impact of socio-economic factors, and broader inclusion of student and family perspectives to foster a genuinely inclusive educational environment.